Emotional processing as mechanism of change in brief good psychiatric management for borderline personality disorder: results of a randomized controlled trial - Ueli Kramer; Loris Grandjean; José Blanco Machinea; Hélène Beuchat; Setareh Ranjbar; Yves de Roten; Jean-Nicolas Despland; Philippe Conus; Stéphane Kolly (BMC Psychiatry)
Abstract Background Borderline Personality Disorder (BPD) is one of the most frequent, severe, mental conditions and is associated with a serious burden of disease. Treatment for patients with BPD involves structured psychotherapy. In addition and in order to improve access to care, psychiatric treatments are available. So far, it remains unclear if brief psychiatric intervention according to Good Psychiatric Management (GPM) produces a reliable effect on a variety of clinical outcomes. The assessment of mechanisms of change contributes to focus the treatment on the essential ingredients of change. The current study aims to demonstrate the emotional processing as a mechanism of change, assessed in an ecologically valid experimental context, of brief GPM. Methods The present two-arm randomized controlled study aims at testing the effects (i.e., reduction in borderline symptoms) and emotional processing as mechanism of change of a brief psychiatric treatment (10 sessions over 4 months), compared with treatment as usual. Participants are N = 76 patients with BPD who are either randomized to a 4 month GPM or a 4 month TAU without any BPD-specific content. All patients undergo assessments of borderline symptoms using ZAN-BPD and experiential enactment for assessment of emotional processing, at intake, 2 months and 4 months (discharge). Results The effect of a brief version of GPM is not different from the effect of TAU on the total score of the ZAN-BPD at 4 month (d = 0.04). At the level of the secondary effects, GPM is more effective in reducing relationship problems on the ZAN-BPD sub-scale (F(1, 61) = 5.53; p = .022, d = 0.52), and in reducing impulsivity and social problems, and it increases treatment retention. Change in emotional processing between intake and month 2 mediates the reduction on the ZAN-BPD subscale relationship problems assessed between months 2 and 4, in an ecologically valid experimental context. Conclusions Overall, brief GPM is not different from TAU in terms of reduction in borderline symptoms, but it may produce reduction in relationship problems between months 2 and 4 into the brief intervention. Change in emotional processing in an experimental context may function as mechanism of change of brief GPM. This study is in line with the top priority of establishing efficacy of brief interventions for BPD and proposes an evidence-based explanation for efficacy. These results should help disseminate brief psychiatric treatments for BPD, which contribute to reduce the societal burden related with BPD. Trial registration Clinical Trials NCT03717818 (date of registration of Abstract October 24th, 2018). Protocol number 2 from February 9th, 2018.